Medical students' perception of scientific research: An experience report on the analysis of Strengths, Weaknesses, Opportunities, and Threats (Research, Society and Development, 2025)
Scientific research is a fundamental component of medical education, supporting critical thinking, evidence-based practice, and professional development. However, medical students often face barriers to engaging in research due to limited institutional support, lack of mentorship, and demanding curricula. This study aims to analyze medical students’ perceptions of scientific research using the SWOT matrix, seeking to contribute to strategies that promote greater student engagement and consolidate a critical, investigative, and evidence-based medical education. Participants from different stages of medical training completed semistructured questionnaires. Qualitative data were analyzed through Bardin’s content analysis and categorized into strengths, weaknesses, opportunities, and threats; quantitative data underwent descriptive statistical analysis. Results indicated strengths such as scientific curiosity, motivation, organization, proactivity, and analytical skills. Weaknesses included difficulties with statistics, scientific writing, hypothesis formulation, limited time, and insufficient qualified mentorship. Opportunities involved the application of research in clinical practice, participation in conferences, scientific initiation programs, and networking. The main threats were lack of institutional support, bureaucratic barriers in ethics committees, academic overload, and financial limitations. Although students recognize the importance of scientific research, structural and educational barriers persist that limit student engagement, highlighting the need to strengthen training in scientific methodology.